Upaya Mengatasi Kesulitan Membaca Permulaan Pada Anak Usia Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
Beginning reading difficulties are a common problem faced by elementary school-aged children in the process of learning to read. This article explores various strategies and approaches that can be used to overcome reading difficulties in the early stages of learning. By introducing appropriate interventions, implementing a variety of teaching methods, and providing the right support, elementary school-aged children can develop strong reading skills from an early age.